Kualitas Buku Teks “Ajar Basa Jawa” Kelas IV SD Berdasarkan Parameter BSNP Dan Uji Fry - Nurhidayati, Nurhidayati; Suwarna, Suwarna; Wulan, Sri Hertanti; Rubiyanto, Yayan (Kamaya: Jurnal Ilmu Agama, 2025)
The assessment of the quality of textbooks is important to be studied in order to measure their suitability to the needs of students and alignment with the curriculum. The Textbook "Ajar Basa Jawa (ABJ)" is a Javanese language subject book used for elementary school students in the Special Region of Yogyakarta. This study uses a qualitative approach based on BNSP parameters and quantitatively based on the readability of the Fry test. The research method in this study is descriptive research. The research instruments consist of (1) the readability quality of the Fry Graph readability parameter and (2) the readability parameter instrument from BSNP. The BSNP parameter book quality instrument consists of the eligibility of (a) content, (b) language, (c) presentation, and (d) graphics. The validity of the data is obtained by the validity technique of diligent and accurate observation, repeated studies, and peer checking. Qualitative analysis with BSNP parameters and quantitative based on Fry Graph. The results (1) based on the Fry Graph analysis, the ABJ book for grade 4 elementary school does not meet the readability as a good grade 4 book. Based on BSNP parameters, the ABJ book is in the less category, and based on the fry test mapping it is more suitable for class 7. This is caused by (a) words with 3-4 syllables, (b) difficult words, (c) various typos/imprecisions by the author, (d) ambiguous words, and (e) sentences that are too long. The use of the Ajar Basa Jawa textbook needs to be aligned with the development of students and the applicable Javanese curriculum in elementary schools.